THE ANALYSIS OF ATTITUDE STRUCTURE DIFFERENCES (COGNITIVE, AFECTIVE, CONATIVE) INTAKO’ CONSUMERS, TANGGULANGIN SIDOARJO - Setyadarma, Bambang; Poernomo, Tri Tjahjo (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2020)
The research objective in this research article aim to understand and examine more deeply the relevance of these consumer attitudes as a basic concept to satisfy the various needs of a consumer in an integrated and organized manner in the field. The research sampling used a cluster sampling approach (Cooper & Emory, 1995), divided into 3 clusters: cognitive cluster (25 participants), affective cluster (25 participants), conative cluster (25 participants) as regular consumers of INTAKO products Tanggulangin, Sidoarjo. The research hypothesis can be accepted factually. Based on the grouping of the three components of attitude above, the writer can conclude that it is the cognitive component that plays a greater role in consumers when they want to make a purchase decision for a product or service. This reality has closed relevance to social phenomena that are generally accepted in various circles of society.